Sports-related facial trauma in the Indian population - A systematic review - S Shreya; Shridhar Damodar Baliga; Sulakshana Shridhar Baliga (Wolters Kluwer Medknow Publications, 2022)
Background: Sports injuries are a growing concern which requires immediate attention. Dental injuries are the most common type of orofacial injuries sustained during sports activities. Objectives: This study aims to review the prevalence of sports-related facial trauma in India, to identify the most common types of oro-facial injury incurred due to sports, and to assess the level of awareness regarding preventive measures used in sports. Methodology: The present review was performed in accordance with preferred reporting items for systematic reviews and meta-analyses guidelines. All articles published from 2005 to 2019 on sports-related facial trauma were analyzed. PubMed, Google Scholar, and Cochrane reviews databases were searched using primary keywords. Results: A total of 24 articles published in the period of 2005-2019 were included. The prevalence of sports-related facial trauma was found to be the highest in the study conducted by Selva et al., in 2018, at a rate of 75%, whereas it was found to be minimal in the study conducted by Bali et al. in 2013. While the awareness of mouthguards was reported the highest in a study conducted by Ramagoni et al., in 2007. Conclusion: This study shows that there is a definite need to improve the awareness as well as the usage of protective gear, from the level of schooling, where children are introduced to sports. Prevention of sports-related facial trauma is essential to avoid the serious and lifelong consequences which could be the aftermath of such injuries.